2018
DOI: 10.3389/fpls.2018.00828
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Artemisia annua Cinnamyl Alcohol Dehydrogenase Increases Lignin and Coumarin and Reduces Artemisinin and Other Sesquiterpenes

Abstract: Artemisia annua is the only medicinal crop that produces artemisinin for malarial treatment. Herein, we describe the cloning of a cinnamyl alcohol dehydrogenase (AaCAD) from an inbred self-pollinating (SP) A. annua cultivar and its effects on lignin and artemisinin production. A recombinant AaCAD was purified via heterogeneous expression. Enzyme assays showed that the recombinant AaCAD converted p-coumaryl, coniferyl, and sinapyl aldehydes to their corresponding alcohols, which are key intermediates involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 54 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…CAD genes were demonstrated to control lignification in plants [39,40,41]. In agreement with our results, Brachypodium distachyon CAD gene BdCAD1 mutants displayed a reduced CAD activity and lower lignin content [39], suggesting that the CAD activity is positively correlated with the lignin content.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…CAD genes were demonstrated to control lignification in plants [39,40,41]. In agreement with our results, Brachypodium distachyon CAD gene BdCAD1 mutants displayed a reduced CAD activity and lower lignin content [39], suggesting that the CAD activity is positively correlated with the lignin content.…”
Section: Resultssupporting
confidence: 88%
“…In Brassica chinensis , the induced expression of BcCAD1-1 and BcCAD2 could increase the lignification of stems [40]. AaCAD has also been reported to positively enhance lignin formation in Artemisia annua [41]. In summary, these results support that PpCAD2 positively regulates lignin biosynthesis by increasing the CAD activity in the stems, fruit pericarp and leaves of transgenic tomato plants.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The reduction of artemisinin levels in chi1-1 might be explained by lower DHAA levels (Supplementary Table S1), which could be due to either decreased DHAA synthesis or enhanced DHAA degradation, but the connection to the chi1-1 mutation is unclear. The crosstalk between phenylpropanoid and terpenoid metabolism is further highlighted by the report that overexpression of the A. annua CINNAMYL ALCOHOL DEHYDROGENASE results in an increase in lignin and coumarin and a reduction in artemisinin and other sesquiterpenes (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, cinnamyl alcohol dehydrogenase (CAD) protein was found to be exclusive in a callus treated with high PF-68 concentration as compared with optimum PF-68 concentration ( Supplementary Table 4 ). This CAD has been widely characterized, and it is known to play a role in lignin biosynthesis via the conversion of phenylpropenyl aldehydes to alcohols (Ma et al, 2018 ). Suppression of CAD was demonstrated to reduce the lignin content and alter the lignin composition in switchgrass (Fu et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%